Realistic Mathematics Education in the Context of Truck Tires and Marble Games in Elementary School Addition and Subtraction Material - Sabiela, Royana Nafisa; Tamara, Latif Fatul; Permadani, Rohani Anggita; Zuliana, Eka (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
The purpose of this study is to describe students’ activities during realistic mathematics learning using the context of trailer truck wheels and marble games in addition and subtraction material. This research employed a design research method with 23 first-grade students of SD Negeri 3 Krasak, Jepara Regency, Central Java as participants. The findings indicate that the use of trailer truck wheels as concrete media increased students’ activeness and curiosity in understanding the concept of addition. Students were able to redraw the wheels, perform calculations, and match their drawings with real objects, leading to an understanding of addition as a process of combining. Meanwhile, through the marble game, students engaged in learning while playing and understood subtraction as the process of taking away from a whole. Overall, students actively participated and successfully completed the activities, showing that real-world contexts effectively support the understanding of basic arithmetic operations.